2018
DOI: 10.3897/bdj.6.e28593
|View full text |Cite
|
Sign up to set email alerts
|

New records of sharks (Elasmobranchii) from the Andaman and Nicobar Archipelago in India with notes on current checklists

Abstract: The diversity of sharks occurring off the Andaman and Nicobar Archipelago in India has received increased attention in recent years. Yet, available checklists are out of date, often with inaccurate information and a number of commercially important species have not been documented through research and fish landing surveys. Here we report on shark species examined during fish landing surveys conducted from January 2017 to April 2018. Records of twelve previously unreported species from the archipelago are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The presently reported investigation disclosed new distributional records of sharks Heptranchias perlo, Hexanchus griseus and Echinorhinus brucus from the region and confirmed the occurrence of Neoharriotta pinnata from Andaman waters. Rajan et al (2012) has enlisted 64 species of chondrichthyans, subsequently several new sharks and batoids were recorded from exploratory surveys and monitoring catch landing of commercial fishing vessesls operated in the region and landed in A&N, Islands, India (Rajan et al 2013, 2016, Devi and Kumaralingam 2014Kumar et al 2015, 2016, Pradeep et al 2016, 2018, Vinu et al 2017 and one recent noteworthy study from the region added 12 sharks to Andaman fauna and added 2 sharks to Indian elasmobranch fauna (Tyabji et al 2018). However, these studies does not include currently reported species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presently reported investigation disclosed new distributional records of sharks Heptranchias perlo, Hexanchus griseus and Echinorhinus brucus from the region and confirmed the occurrence of Neoharriotta pinnata from Andaman waters. Rajan et al (2012) has enlisted 64 species of chondrichthyans, subsequently several new sharks and batoids were recorded from exploratory surveys and monitoring catch landing of commercial fishing vessesls operated in the region and landed in A&N, Islands, India (Rajan et al 2013, 2016, Devi and Kumaralingam 2014Kumar et al 2015, 2016, Pradeep et al 2016, 2018, Vinu et al 2017 and one recent noteworthy study from the region added 12 sharks to Andaman fauna and added 2 sharks to Indian elasmobranch fauna (Tyabji et al 2018). However, these studies does not include currently reported species.…”
Section: Discussionmentioning
confidence: 99%
“…Except for checklists and few new reports from waters around the Andaman and Nicobar Islands of India (Soundararajan and Roy 2004, Rajan et al 2012, 2013, 2016, Devi and Kumaralingam 2014 chondrichthyan diversity of this region is poorly known. However, considering large information gap in the region more concentrated studies are being conducted in the recent past and several ongoing studies are providing better understanding of faunal diversity, fishery trends and improved catch and species composition (Kumar et al 2015, 2016, Pradeep et al 2016,2018, Vinu et al 2017, Tyabji et al 2018.There is an urgent need to explore this biodiversity hotspot for its better understanding and for conservation actions. Perpetual efforts for documentation of the diversity and updating the checklists with correctly identified species are important for conservation and management of the vulnerable fauna.…”
Section: Introductionmentioning
confidence: 99%
“…Only two species of deep-sea sharks were recorded in this study despite recent additions of seven new records from the region [14, 2325]. This was due to the logistical difficulties in sampling the large quantities of deep-sea sharks landed, along with time constraints between landings and transport to the storage units.…”
Section: Discussionmentioning
confidence: 99%
“…Here, sharks and rays are primarily caught as bycatch [7–11] in a large fishing fleet of 238,772 registered commercial and artisanal fishing crafts [12]. However, a few targeted shark fisheries that formed in the 1980’s remain including in the Andaman and Nicobar Islands [13, 14]. Anecdotal information from interviews with fishers on these islands indicate that shark and ray populations have declined [15] but there have been few systematic surveys of landings carried out to assess the current situation.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the total length of Carcharhinus altimus ranged from 54.62-160.82 cm with an average of 108.47± 34.08 cm. Tyabji et al (2018) said that, 3 male and 1 female of C. altimus in Andaman and Nicobar Archipelago, India was ranged from 90-237.5 taking in consideration. Two of the male specimens ranged in size from 103 to 128 cm.…”
Section: Discussionmentioning
confidence: 99%